Knockdown of mineralocorticoid or angiotensin II type 1 receptor gene expression in the paraventricular nucleus prevents angiotensin II hypertension in rats. (22nd July 2014) - Chen, Aidong; Huang, Bing S.; Wang, Hong‐Wei; Ahmad, Monir; Leenen, Frans H. H.
Abstract : Key points: Chronic subcutaneous infusion of Ang II causes a progressive increase in blood pressure (BP) associated with significant increases in angiotensin type 1 receptor (AT1 R) and mineralocorticoid receptor (MR) expression in hypothalamic nuclei. Intra‐paraventricular nucleus (PVN) infusion of AAV‐ AT1a R‐siRNA or of AAV‐MR‐siRNA markedly knockdown AT1a ‐R or MR expression in the PVN but not in the subfornical organ; or supraoptic nucleus, and prevent most of the increase in BP. These findings indicate that increased MR and AT1 R activation in the PVN play a critical role in Ang II‐induced hypertension in rats on regular salt intake. Abstract: Circulating Ang II activates an aldosterone‐mineralocorticoid receptor (MR) – angiotensin II (Ang II) – angiotensin type 1 receptor (AT1 R) pathway in the hypothalamus. To obtain insights into the actual neuronal projections involved, adeno‐associated virus carrying small interfering RNA against either AT1a R (AAV‐AT1a R‐siRNA) or MR (AAV‐MR‐siRNA) were infused into the paraventricular nucleus (PVN) in Wistar rats. Intra‐PVN infusion of AAV‐AT1a R‐siRNA or AAV‐MR‐siRNA decreased AT1 R or MR expression in the PVN but not in the subfornical organ (SFO) or supraoptic nucleus (SON). Subcutaneous infusion of Ang II at 500 ng kg −1  min −1 for 2 weeks increased mean arterial pressure by 60–70 mmHg, and increased AT1 R and MR expression in the SFO, SON and PVN. Intra‐PVN AT1a R‐siRNA prevented the Ang II‐induced increase in AT1 R but not MR expression in the PVN, and MR‐siRNA prevented MR but not AT1 R expression in the PVN. The increases in AT1 R and MR expression in both the SFO and the SON were not changed by the two AAV‐siRNAs. Specific knockdown of AT1 R or MR in the PVN by AAV‐siRNA each prevented most of the Ang II‐induced hypertension. Prevention of the subcutaneous Ang II‐induced increase in MR but not the increase in AT1 R by knockdown of MR and vice versa suggests an independent regulation of MR and AT1 R expression in the PVN. Both AT1 R and MR activation in the PVN play a critical role in Ang II‐induced hypertension in rats.